INDIKASI BEDAH KATARAK DI POLIKLINIK MATA BLU RSUP PROF. Dr. R.D. KANDOU MANADO - Indra, Charles; Sumual, Harry J. G.; Rares, Laya M. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: According to the World Health Organization (WHO), cataracts are the leading cause of blindness and visual impairment throughout the world. Cataract surgical indications are classified into three groups: 1) visual acuity rehabilitation, 2) medical indications, and 3) cosmetic indications. This study aimed to obtain the indications for cataract surgery at the Ophthalmology Department of Prof. Dr. R.D. Kandou Hospital Manado. This was a descriptive retrospective study. Data were collected from the medical records at the Ophthalmology Department of Prof. Dr. R.D. Kandou Hospital. The results showed that there were 84 cataract patients who underwent cataract surgery from January to June 2012. Based on the indications of cataracts surgery, visual acuity rehabilitation were found in 81 cases (96.43%) and medical indications in 3 cases (3.57%). Conclusion: In these results, it was found that the most cases requiring cataract surgery were in the group: visual acuity rehabilitation. Cosmetic indication was not found in this study. Keywords: cataract, surgery, indication. Â Â Abstrak: Berdasarkan WHO, katarak merupakan penyebab utama kebutaan dan gangguan penglihatan di dunia. Terdapat tiga kelompok indikasi bedah katarak, yaitu: 1) rehabilitasi ketajaman penglihatan, 2) indikasi medis, dan 3) indikasi kosmetik. Penelitian ini bertujuan untuk mengetahui indikasi yang mendorong dilakukannya bedah katarak di Poliklinik Mata BLU RSUP Prof. Dr. R.D. Kandou Manado. Penelitian ini bersifat deskriptif retrospektif dengan menggunakan data dari catatan medis di Poliklinik Mata BLU RSUP Prof. Dr. R.D. Kandou Manado. Hasil penelitian memperlihatkan bahwa terdapat 84 kasus bedah katarak periode Januari-Juni 2012. Berdasarkan indikasi bedah katarak terdapat 81 kasus (96,43%) dengan indikasi rehabilitasi ketajaman penglihatan dan 3 kasus (3,57%) dengan indikasi medis. Simpulan: Indikasi bedah katarak yang paling sering ditemukan di Poliklinik Mata BLU RSUP Prof. Dr. R.D. Kandou Manado ialah rehabilitasi ketajaman penglihatan. Indikasi kosmetik tidak ditemukan dalam penelitian ini. Kata kunci: katarak, indikasi, bedah.